Smart conveyor/ W. M. W. I. W. Ramli, N. A. Bharu and N. F. Zulkefli - Ramli, W. M. W. I. W.; Bharu, N. A.; Zulkefli, N. F. (2018)
The Smart Conveyor is a project of a conveyor application with the adaptation of sensor to make it operate smartly and met the concept of Smart Campus. The Smart Conveyor is going to be mounted at the cafeterias in the campus and college. The function of the smart conveyor is to maximize the efficiency of works in order to ensure the dirty dishes and utensils are managed systematically. Besides that, it is also to keep the cleanliness at the cafeteria so that the students and staff can have their meal comfortably. The main components of the smart conveyor are Arduino UNO, Ultrasonic Sensor, DC motor and L293D IC. Arduino UNO is the core of this project and it is very important to make sure the project can run as expected. If the program gone wrong, it may affect the operation of the motor. The Ultrasonic Sensor is used to detect the plate on the conveyor. When the Ultrasonic Sensor has detected the plate on the conveyor, it will send the signal to the Arduino UNO and the input signal will be send to L293D IC. L293D IC functions as a switch to the circuit to turn on and off the motor. The conveyor will carry the dirty plate from the front of the café straight to the kitchen after someone put the plate on the conveyor. In conclusion, this project will definitely reduce the human’s energy and also will make the work more efficient yet easy from before.